PENDAMPINGAN TRADISI BURDAH KELILING DI MASJID BAROKATUL HASAN NOGOSAREN GADING PROBOLINGGO - Jamiatun Nasikhah; Aziziyah Masfiyatul (Kalam Nusantara Institute, 2023)
This article examines the tradition of reading Burdah compiled by the Egyptian poet Muhammad bin Sa'id al-Bushiri (d. 1295) with a collection of poems about the life history of the Prophet Muhammad. This assistance uses the ABCD method through mentoring the religious activities of students at the Barokatul Hasan mosque, Wonosari Nogosaren Gading Probolinggo hamlet, where this tradition has just been implemented in Wonosari hamlet. This traveling Burdah reading is an effort by PENDAMPINGAN students to provide a quick method of memorizing Burdah readings to students and fortify the environment so that they are always given safety, including from the threat of the corona virus outbreak which is currently endemic and increasing welfare through assistance to the community.